Evaluation of Cymbopogon schoenanthus essential oil in lambs experimentally infected with Haemonchus contortus - Katiki, L. M.; Chagas, A. C. S.; Takahira, Regina Kiomi [UNESP]; Juliani, H. R.; Ferreira, J. F. S.; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B.V., 2012)
Hematophagous gastrointestinal parasites cause significant economic losses in small ruminant grazing systems. The growing reports of multi-drug resistant parasites call for intensive research on alternative treatments for anthelmintics to help small ruminants cope with these parasites. Two-month-old lambs with mean body weight (BW) of 22.5 kg were experimentally infected with a multidrug-resistant Haemonchus contortus strain. Infected animals were dosed orally with Cymbopogon schoenanthus essential oil to evaluate its anthelmintic potential. Eighteen animals were allocated into three groups of six animals, and each received one of the following treatments: Group 1 - control (10 mL of water), Group 2 - C. schoenanthus essential oil (180 mg/kg BW); and Group 3 - C schoenanthus essential oil (360 mg/kg BW). Animals received the oil once a day for 3 consecutive days. Lambs were evaluated clinically for blood biochemistry before, at 1, 5, 10, 15 and 20 days after treatment, and then were euthanized to assess the total worm burden. No statistically significant reduction in fecal egg count, packed cell volume or total worm count was observed after treatments. Also, no statistical difference among group means for blood levels of urea, creatinine, albumin, alkaline phosphatase, aspartate aminotransferase and gamma glutamyl transferase was found. Larval development assay (LDA) and egg hatch assay (EHA) were performed from feces of treated animals at 1, 5, 10 and 15 days after essential oil administration. An inhibition in LDA was observed 1 day after the 3-day treatment in larvae from feces of animals treated with 360 mg/kg essential oil. In conclusion, the essential oil at the doses of 180 mg/kg and 360 mg/kg was safe to sheep, but failed as an anthelmintic treatment when applied to young sheep artificially infected with a multidrug-resistant H. contortus strain. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cymbopogon schoenanthus; Essential oil; Haemonchus contortus; Small ruminant; Anthelmintic; Nematicide